PRACTICUM IMPLEMENTATION ANALYSIS IN CHEMISTRY LEARNING IN HIGH SCHOOL IN BANDA ACEH - Hilda Yusmarina; Latifah Hanum; Ratu Fazlia Inda Rahmayani (FKIP USK, 2021)
It has been conducted a research entitled